The Wild Hunt Divinations : A Grimoire - Ketner, Trevor, 1991- (Book collections on Project MUSE., 2023)
"Shakespeare's 154 sonnets anagrammed into wildly new poems about queer desire and kinkThe Wild Hunt Divinations: A Grimoire is a stunning second collection from National Poetry Series winner, Trevor Ketner. Comprised of 154 sonnets, each anagrammed line-by-line from Shakespeare's sonnets, the book refracts these lines through the thematic lens of transness, queer desire, kink, and British paganism. The sonnets come together to form a grimoire that casts a trancelike and intense spell on the reader. Centered on love and desire in the English canon, this collection speaks to the ever-emerging and beautiful manifestations of queer love and desire. Relentless, excessive, wild, and tender, The Wild Hunt Divinations: A Grimoire sets itself to chanting from beginning to end"--